Pendampingan Belajar Al-Qur'an: Solusi Peningkatan Literasi Al-Qur'an Santri TPQ Nawwiyatul Ikhsan Sidoarjo - Yusrenicha Retna Ningsih (JPPMI: Jurnal Pelayanan dan Pemberdayaan Masyarakat Indonesia, 2026)
This community service aims to describe the implementation of Qur’an learning assistance activities at TPQ Nawwiyatul Ikhsan Sidoarjo and to evaluate its effectiveness in improving students’ ability to read the Qur’an. This study uses a qualitative approach with the Participatory Action Research (PAR) method, which emphasizes active involvement between the researcher, ustadzah (female teacher), and 20 students in the learning process. The mentoring activities are carried out systematically through several stages, such as reading practice, tajwid instruction, and tiered evaluation using the Ummi method. The findings show an improvement in students’ reading fluency, understanding of tajwid, and learning motivation. Before the mentoring program, some students were not yet fluent in reading the Qur’an; after the program, their reading ability improved. A conducive and interactive learning environment also contributes to increasing students’ confidence. In addition, parental involvement is one of the main supporting factors for the success of the program. Therefore, Qur’an learning assistance based on collaboration and a participatory approach is considered effective in improving Qur’anic literacy as well as forming positive character among students